The generality of strength adaptation - Buckner, S. L.; Kuehne, T. E.; Yitzchaki, N.; Zhu, W. G.; Humphries, M. N.; Loenneke, J. P. (Journal of Trainology, 2019)
The generality of strength suggests that a "strong" individual will typically exhibit higher values of strength across a wide range of strength tasks for a given muscle relative to their weaker counterpart. This concept is often extended to adaptation, suggesting that increasing strength on a given movement or strength task with a given muscle should reflect an increase in other movements or tasks using that same muscle. The concept of a generality of strength adaptation appears less supported in the literature. Objective: To elaborate on recommendations for strength assessment, providing a focus on the "generality of strength" and the "generality of strength adaptation."Design & Methods: We reviewed the literature on a generality of strength. In addition, we examined the resistance training lit erature to provide evidence and discussion on a generality of strength adaptation. Results/Conclusions: The generality of strength adaptation, even across strength skills using the same muscle on related movements seems quite low. Although some studies show a weak generality of strength adaptation and others show no generality of strength adaptation, it appears that increases in strength diminish as the strength assessment becomes farther removed from the actual training stimulus.